Retrofit assessment of masonry buildings through simplified structural analysis - Mariateresa Guadagnuolo; Marianna Aurilio; Giuseppe Faella (Fracture and Structural Integrity)
The current seismic prevention strategy is based on a unitary approach aimed at a risk mitigation, also at territorial level. The Italian guidelines for the assessment and mitigation of seismic risk of cultural heritage provides indications for the seismic analysis of protected cultural heritage, with the aim of specifying a path of knowledge, assessing the level of safety and planning possible improvements. The Italian building heritage is very vast and heterogeneous and was devastated by earthquakes due to its high vulnerability; therefore, the seismic risk mitigation also requires the availability of simple and handy analysis tools. The aim of this paper is the illustration of an easy, although approximate, procedure for the evaluation of the seismic safety index and the optimization of strengthening interventions. The procedure is applied to buildings located in the province of Caserta. The analyses are performed with reference to two types of buildings that are particularly recurrent and representative of the building heritage of this area and placed in areas with different seismic hazard.